The Influence Of E-Trust And E-Service Quality On Customer Loyalty Of Access Application Users By KAI With Customer Satisfaction As An Intervening Variable - Lusiana Rahmawati; Sonja Andarini (Jurnal Ekonomi dan Bisnis Digital, 2024)
The rapid progression of digitization has revolutionized various sectors, including transportation. Several offline services have switched to online services in the form of applications. The high risk of online transactions can involve e-trust and e-service quality to achieve customer satisfaction with application users. This study investigates the influence of e-trust and e-service quality on customer loyalty in the Access by KAI application, with customer satisfaction as an intervening variable. Addressing user complaints, such as system errors and scheduling issues, the research explores how these factors affect customer loyalty. The study adopts a quantitative associative approach, surveying 160 KAI Access users in Surabaya, analyzed using the SEM-PLS method. Results indicate that e-service quality significantly impacts customer satisfaction and loyalty, while e-trust influences satisfaction but not loyalty directly. Customer satisfaction plays a critical role as an intervening variable, bridging e-trust and e-service quality with loyalty. The R-Square analysis reveals a moderate explanatory power for customer satisfaction (50%) and a strong explanatory power for customer loyalty (75%). Despite advancements in features like trip planners and live tracking, user complaints highlight areas needing improvement. The study concludes that enhancing e-service quality and resolving technical issues can strengthen customer loyalty, emphasizing the pivotal role of customer satisfaction. This research provides insights for PT Kereta Api Indonesia to optimize digital innovations and improve service quality, reinforcing customer trust and satisfaction in digital transportation platforms.